Carbon fiber/epoxy composite laminates as through-thickness thermoelectric generators. (22nd March 2022) - Karalis, George; Tzounis, Lazaros; Tsirka, Kyriaki; Mytafides, Christos K.; Liebscher, Marco; Paipetis, Alkiviadis S.
Abstract: This research study demonstrates a carbon fiber reinforced polymer (CFRP) composite laminate with an embedded thermoelectric (TE) enabled glass fiber (GF) ply. The TE-enabled GF functional ply was purposely laminated to create a structural through-thickness thermoelectric generator (TEG). Simultaneously, the highly conductive carbon fiber (CF) reinforcing phase served as electrodes for the device. Tellurium nanowires (NWs) were incorporated in various mass ratios in a PEDOT:PSS matrix to produce different TE pastes. The TE pastes were deposited on the GF fabrics via a facile blade coating technique. The highest power factor (57.2 μW/m . K 2, in-plane Seebeck coefficient +189 μV/K) was exhibited by the coating formed by the paste with a specific mass ratio of 1:1 (Te NWs to PEDOT:PSS). The TE-enabled GF plies were employed for the manufacturing of both 10-ply unidirectional (UD), and cross-ply composite laminates. The UD laminate generated a TE voltage ( V TEG ) of 8.4 mV and a TE current (Isc ) of 597.4 μA for 100 K through-thickness temperature difference (Δ T ) i.e., a maximum power of 1.3 μW. The temperature sensing capability of the TEG-laminate was also demonstrated. Three-point bending tests indicated a ca. 10% decrease in flexural properties with the integration of the TEG functionality for the UD configuration. Graphical abstract: Image 1 Highlights: TE-enabled GF functional ply with 57.2 μW/m . K 2 power factor. Through-thickness TEG-CFRP laminate device with 1.3 μW power output. Through-thickness TEG-CFRP laminate device with 0.1 W/m 2 power density. Multifunctional CFRP laminate with self-powered temperature sensing capabilities.